Efektivitas Blood Flow Restriction Exercise Dalam Peningkatan Quadricep Strength Pada Pasien Post Acl Rekonstruksi : Literature Review - Ginting, Auvin Joe (Jurnal Fisioterapi Terapan Indonesia, 2024)
This article aims to evaluate the Effectiveness of Blood Flow Restriction Exercise in Improving Quadriceps Strength in Patients with ACL Reconstruction. This project is a literature study in narrative form. The background for conducting this research is the high incidence of ACL tears, ranging from 78 to 81 cases per 100,000 population worldwide in a year. The most common surgical treatment provided is ACL reconstruction. Quadriceps strength reduction after 6 months post-operation reaches 20% compared to pre-operation. From the symptoms and clinical complaints of quadriceps muscle weakness, one of the interventions that can be performed is Blood Flow Restriction Exercise. A search was conducted using various databases, resulting in the discovery of 10 articles, which were then filtered and selected to obtain 7 articles. Rresulting in a final selection of 5 articles. The objective of this study is to determine the effectiveness, dosage, and success factors of BFRE in improving quadriceps muscle strength in patients post-ACL reconstruction using isokinetic and isometric dynamometers. Research results showed an increase in quadriceps muscle strength, even in knee function. The dosage provided varied but still had a positive impact. In conclusion, the administration of BFRE can be an intervention solution to improve quadriceps muscle strength in patients post-ACL reconstruction.